2019
DOI: 10.1016/j.neunet.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Dreaming neural networks: Forgetting spurious memories and reinforcing pure ones

Abstract: The standard Hopfield model for associative neural networks accounts for biological Hebbian learning and acts as the harmonic oscillator for pattern recognition, however its maximal storage capacity is α ∼ 0.14, far from the theoretical bound for symmetric networks, i.e. α = 1. Inspired by sleeping and dreaming mechanisms in mammal brains, we propose an extension of this model displaying the standard on-line (awake) learning mechanism (that allows the storage of external information in terms of patterns) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 63 publications
(139 reference statements)
6
68
0
12
Order By: Relevance
“…the standard equivalence between Hopfield models and two-layers Boltzmann machines [16,18]), layer is equipped with imaginary real-valued neurons (best suitable to perform spectral analysis 10 ). As a consequence, the resulting interpolating architecture is rather tricky, by far richer than its classical limit yet it turns out to be managable and actually a sum rule for the quenched free energy related to the model can be written and even integrated, under the assumption of replica symmetry: such an expression, as well as those stemming from its extremization for the order parameters, sharply coincides with previous results [33], confirming them in each detail.…”
Section: Conclusion and Outlookssupporting
confidence: 80%
See 4 more Smart Citations
“…the standard equivalence between Hopfield models and two-layers Boltzmann machines [16,18]), layer is equipped with imaginary real-valued neurons (best suitable to perform spectral analysis 10 ). As a consequence, the resulting interpolating architecture is rather tricky, by far richer than its classical limit yet it turns out to be managable and actually a sum rule for the quenched free energy related to the model can be written and even integrated, under the assumption of replica symmetry: such an expression, as well as those stemming from its extremization for the order parameters, sharply coincides with previous results [33], confirming them in each detail.…”
Section: Conclusion and Outlookssupporting
confidence: 80%
“…In the current work we mathematically described the phenomena of reinforcement and remotion, as pioneered by Crick & Mitchinson [29], by Hopfield [40] and by many others in the neuroscience literature, see e.g [30,38,47,48]): interestingly, such mechanisms have been evidenced to lead to an improvement of the retrieval capacity of the system. In particular, in [33], we showed that the system reaches the expected upper critical capacity α c = 1, still preserving robustness with respect to fast noise. However, the statistical mechanical analysis, set at the standard replica symmetric level of description, was carried out via non-rigorous approaches (e.g., replica trick and numerical simulations).…”
Section: Conclusion and Outlooksmentioning
confidence: 77%
See 3 more Smart Citations